Ceria substrate–oxide composites as catalyst for highly efficient catalytic oxidation of NO by O2. (15th February 2016) - Wang, Zhihua; Lin, Fawei; Jiang, Shudong; Qiu, Kunzan; Kuang, Min; Whiddon, Ron; Cen, Kefa
Graphical abstract: Highlights: A series of ceria substrate–oxide composites catalysts were investigated. The highest NO conversion efficiency of 93% could be yielded over Ce–Co catalyst. Detailed characterization was performed through BET, XRD, H2 -TPR, TEM, and XPS. 53% NO conversion was obtained at 190 °C when 200 ppm SO2 and 3% H2 O were added. Abstract: Oxidation catalysts can be used to achieve highly efficient NO oxidation by residual O2 in flue gas and decrease the power consumption of pollutant oxidation process through ozone injection. Ceria was selected as the catalyst carrier because of its excellent oxygen storage capacity. Ceria substrate composite catalysts were prepared through sol–gel method. The effects of dopant metals (Co, Mn, Fe, Cr, and Ni), calcination temperatures, and Co doping content on NO conversion efficiency were assessed. The physico-chemical characteristics of catalysts prepared were analyzed through BET, XRD, TPR, TEM, and XPS. Cobalt was used as the dopant metal because of its excellent catalytic activity. The optimal condition was 400 °C calcination, and the effective mole ratio of Co to Ce was 0.51. Under the optimal condition, the Ce–Co composite catalyst yielded an NO conversion efficiency of 93% at 230 °C. The catalytic activity of the Ce–Co composite catalyst on NO oxidization was related to structural features, crystalline pattern, redox ability, and interactions between cobalt and ceria. The effect of residual oxygen concentration in flue gas on NO oxidation was evaluated. When the oxygen concentration exceeded 6%, NO conversion efficiency stabilized. The sulfur- and water-resistant ability of the Ce–Co composite catalyst was very weak. Only 53% NO conversion was obtained at 190 °C when 200 ppm SO2 and 3% steam were added.